2020
DOI: 10.1556/650.2020.31930
|View full text |Cite
|
Sign up to set email alerts
|

Orvos-beteg kommunikációs gyakorlat szimulált pácienssel a koronavírus-járvány idején. (A COVID–19-pandémia orvosszakmai kérdései)

Abstract: Absztrakt: Bevezetés: A koronavírus-járvány okozta veszélyhelyzet idején a Szegedi Tudományegyetemen a negyedéves orvostanhallgatók Orvos-beteg kommunikációs gyakorlata is online történt. A gyakorlat a videóanalízis módszerén alapul, szimulált páciensek bevonásával történik, kiemelt hangsúlyt fektetve a személyközi interakciókra, így az online megvalósítás rendkívül nagy kihívást jelentett. Célk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Mohos et al found the transfer of their course to an online environment to be a success, with consistent outcomes compared with previous semesters. Nevertheless, they raised concerns considering the missing personal contact (25), which we came across as well.…”
Section: Was the Taking Of The Sexual History When Comparing On-site With Online Learningmentioning
confidence: 99%
“…Mohos et al found the transfer of their course to an online environment to be a success, with consistent outcomes compared with previous semesters. Nevertheless, they raised concerns considering the missing personal contact (25), which we came across as well.…”
Section: Was the Taking Of The Sexual History When Comparing On-site With Online Learningmentioning
confidence: 99%
“…Az Egyesült Államokban és NyugatEurópában a kommunikációs készségfejlesztő tréningek több mint fél évszázada a medikusképzés szerves részét képezik [8]; az orvosbeteg interakció oktatásában a kifejezetten játékon keresztüli fejlesztés az USAban már 2008 óta jelen van [9,10], az üzleti/menedzsment oktatás pedig 1999 óta kínál kurzusokat és intenzív workshopokat az üzleti/me nedzseri improvizációról [11].…”
Section: Eredeti Közleményunclassified
“… 38 The challenges treating “difficult” patients are also discussed in Szili’s work, 39 as well as the necessity of using the appropriate politeness techniques to encourage closer cooperation between the participants, even in online consultations. 40 Our SP program helps to meet the above requirements, and fills the gap in SP literature by the opportunities of diverse integration it provides.…”
Section: Introductionmentioning
confidence: 99%